Analysis of Determining Factors of Student Satisfaction at Klabat University - Walean, Ronny H.; Kainde, Sandra; Lapian, Waya Shandy; Manarisip, Flora (8ISC Abstract Proceedings; 8ISC Abstract Proceedings, 2022)
The purpose of this study was to determine the factors that influence student satisfaction at Klabat University, Airmadidi North Minahasa, North Sulawesi. This study uses the Explanatory Factor Analysis method. The participants in this study were active students of Klabat University in the even semester of the 2019/2020 academic year. There are 51 variables obtained through in-depth interviews with 16 respondents and followed by a survey of 394 students. Exploratory factor analysis using the principal factor extraction method revealed that there are 10 factors that influence student satisfaction. These factors are Vespers spiritual activities, students can graduate early, lecturers provide time for consultation, campus day activities, a clean environment, a sense of helping fellow students, regional cultural performances, vegetables, and fruit in the cafeteria, student organizations, and smoke-free campus. The highest variance that affects student satisfaction at the University of Klabat is vespers' spiritual activities, while the lowest variance is a smoke-free campus. Keywords : Student Satisfaction, Klabat University, Klabat University Student Satisfaction